Factors Influencing Poverty in South Africa: Time Series Analysis - Dagume, Mbulaheni Albert (International Journal of Economics and Financial Issues, 2021)
Poverty is an emerging issue that is being debated upon in both developed and developing countries, including South Africa. This research investigates the factors that affect poverty in South Africa, as well as the theoretical connections between poverty and the country’s key macroeconomic variables using annual time series data for 1996-2019. The stationarity test found that some variables were not stationary at the level but were after first differencing; the cointegration test demonstrated that the variables under investigation have a long-term relationship. The VECM findings revealed that the ratio of agriculture to GDP has a negative short-run relationship with poverty rates, while domestic credit to the private sector, foreign direct investment, growth rate, and gross enrollment ratio have a negative short-run relationship with poverty rate, but statistically significant. Domestic credit to the private sector, foreign direct investment, growth rate, and gross enrollment ratio all have a negative long-run relationship with poverty rate, while agriculture to GDP and military spending have a positive but statistically insignificant long-run relationship with poverty rate. To encourage more private sector investment in economic development and poverty alleviation, the South African government must create an open business climate with attractive regulatory incentives. Keywords: Lower bound poverty line, Foreign Direct Investment, Economic Growth, SA JEL Classifications: C22, C50, E60, E62 DOI: https://doi.org/10.32479/ijefi.11629